O espaço divino no discurso de Ezequiel nos capítulos 8 a11 e 43 a 48 - Kunz, Marivete Zanoni (2012)
The current research consists in an analysis on the subject "Divine space in the speech of Ezekiel in the chapters 8 to 11 and 43 to 48". The research will make an examination of the matter from the semiotic proposal of Greimas, with the objective of understanding better the text and the search for some possibilities of significance for the space in this speech. The first chapter will make a verification of concepts about this matter, in both biblical areas and other thinkers not related to the theological area, but to the Science of Religion. The analysis of the chapters will be presented after a brief exposition of basic questions related to the method which was used. The objective of this first chapter is to verify some approaches of space on the question of holy and profane. In this work, there s also a description of concepts about space, starting from the Hebrew biblical word, as the observation of the space considered sacred to the Jewish people. After, using semiotics, two groups of text in the book of the prophet Ezekiel will be analyzed. Also, in the texts, essential aspects will be considered in the semio-discursive reading, for example, the emphasis on the object of value, narrative path of the text and the semiotic square. The analysis of the plan of expression or discursive level will be highlighted, which will verify the segmentation and the structure of the space, the function of the subject and others. In the analysis of the plan of expression internal texts and intertextuality will be verified. In the analysis of the plan of content, the figurative theme path will be checked and the fundamental speech structure. The aim is a verification and the arrival at a meaning of a space sense in the selected texts in the book of Ezekiel, as well as how the space is characterized in those groups. This study will also consider points of the exegetics analysis of a text, to describe better the texts studied.